Prognostic value of FFRCT in patients with stable chest pain – a 3-year follow-up of the ADVANCE-DK registry. (3rd October 2022) - Madsen, K T; Noergaard, B L; Oevrehus, K A; Parner, E; Jensen, J M; Grove, E L; Fairbairn, T A; Nieman, K; Patel, M; Rogers, C; Mickley, H; Rohold, A; et al.
Abstract: Introduction: The short-term safety of using coronary CT angiography (CTA) derived fractional flow reserve (FFRCT) to guide downstream testing after CTA is well documented. Whether the prognostic information provided by FFRCT can be extended to sustained follow-up and to patients with a high degree of coronary artery calcification (CAC) is unknown. Purpose: To evaluate the association between FFRCT and clinical outcomes in new onset stable symptomatic patients with coronary stenosis up to 3 years after CTA index testing. Methods: Multicenter 3-year follow-up study of 900 patients from the Assessing Diagnostic Value of Non-invasive FFRCT in Coronary Care (ADVANCE) registry at three Danish sites, the "ADVANCE-DK Registry". All patients had at least one ≥30% coronary stenosis by CTA and underwent subsequent core laboratory FFRCT analysis by HeartFlow. The criterium for an abnormal FFRCT test result was an FFRCT value ≤0.80 (2 cm distal to stenosis). High CAC was defined as a CAC score ≥400. The primary endpoint (PE) was a composite of all-cause death and spontaneous myocardial infarction (MI). The secondary endpoint (SE) was a composite of cardiovascular (CV) death and spontaneous MI. Events were adjudicated by an independent clinical committee. Results: Patient characteristics are given in Table 1. Coronary stenosis ≥50% was present in 750 (83%) patients. In total 36 patients suffered a PE (all-cause death, n=24; MI, n=12) and 22 an SE (CV death, n=10; MI, n=12). An abnormal vs a normal FFRCT test result was associated with an increased risk of the PE and of the SE both overall and in patients with high CAC; PE (all), 6.6% vs 2.1%, relative risk (RR): 3.1; 95% CI: 1.6–6.3, p<0.001, SE (all), 5.0% vs 0.6%, RR: 8.7; 95% CI: non assessable, p<0.001, PE (high CAC), 9.0% vs 2.2%, RR: 4.1; 85% CI: 1.4–11.8, p=0.001, and SE (high CAC), 6.6% vs 0.5%, RR: 12.0; 95% CI: non assessable, p=0.01, respectively, Figure 1. The observed increased risk in patients with an abnormal vs a normal FFRCT test result persisted after adjustment for degree of stenosis by CCTA (< / ≥50%) and amount of CAC (< / ≥400): PE, adjusted RR: 2.5; 95% CI: 1.2–5.2, p=0.02, and SE, adjusted RR: 8.0; 95% CI: 2.1–30.2, p=0.002. Conclusion: Patients with stable chest pain, stenosis by CTA and a normal FFRCT test result have a low risk of adverse outcomes during 3 years of follow-up. An abnormal FFRCT identifies patients at increased risk of death or spontaneous MI. These associations are consistent in patients with high levels of CAC. Funding Acknowledgement: Type of funding sources: None.